zipRealty : leading a start-up to the next level (B) - Chatman, Jennifer (London : SAGE Publications Ltd, 2017)
Start-up company zipRealty is a real estate brokerage that leveraged the Internet on the belief that selling or buying a home could be faster, easier, and more efficient than was possible with existing approaches to residential home transactions. Despite zipRealtys successes, the company experienced a series of external and internal challenges.
Originally published in Chatman, J. (2001). zipRealty: Leading a start-up to the next level (B). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; zipRealty; Organizational behavior; Business planning; Real estate business